Pembaharuan Lembaga Pendidikan Islam di Pondok Pesantren - Meilisa Putri; Ahmad Rivauzi (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to look at the renewal of Islamic educational institutions in the Light-light Nurul Yaqin Islamic Boarding School, which consists of foundations, formal and non-formal institutions. This study uses a qualitative method with a descriptive approach. Sources of data were taken through direct interviews with informants consisting of the Caliph, the Head of the Pondok, Deputy Curriculum for the cottage, the Daily Executive of the El Imraniyah Islamic Development Foundation, and the educators of the Nurul Yaqin Islamic Boarding School. To strengthen the data, researchers also took data through observation and documentation. Overall, the results of the study showed that the renewal of Islamic education in terms of institutions at the Light-light Nurul Yaqin Islamic Boarding School did not experience many changes, but in the formal institutions of Islamic boarding schools officially made the Bustanul Muahaqqiqin and Mudaqqiqin classes which were formerly non-formal institutions, changed their status to the formal institution in 2021 under the name Ma'had Aly.